Chapter Development of a sustainable accessibility model for the Marine Protected Area Gaiola Underwater Park, in Naples, Italy - Simeone, Maurizio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Marine Protected Area Gaiola Underwater Park was instituted in 2002 for the preservation of natural and archaeological aspects. Due to the urban context, the anthropic pressure has always been high and it has always undermined the preservation of the cultural and environmental heritage. The public beach in the General Reserve has always been impacted by great problems of overcrowding. The safety problems highlighted by the pandemic drove the Manager Authority to apply a new model of accessibility. This work aims to show and discuss the results obtained with this new fruition model.